New Perspectives in Network Studies A Multidisciplinary Approach - Moretti, Anna.; Balzarin, Lisa. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
In line with the multi-disciplinary nature of network research, this edited volume collects both empirical and conceptual contributions that nurture the debate on network research, specifically dealing with the topics of network performance and agency. The contributions draw on different literatures and epistemic approaches and address different levels of analysis, both from a static and a dynamic point of view. It will be of great interest to academics and students developing research in the field of network studies. It will also be of interest to scholars of operations management, organization studies, strategy, innovation, financial management and business history. Anna Moretti is an Associate Professor in the Department of Management at Ca 'Foscari University of Venice, Italy. Lisa Balzarin is a Research Fellow in the Department of Management at Ca 'Foscari University of Venice, Italy.
Table of contents -- Introduction by the editors -- Section I: Network as metaphors -- 1. "A Structured Literature Review on Networks and Organizations" by Anna Moretti and Marco Tolotti -- 2. A game-theoretic approach for managing origin-to-destination network flow with path preferences and velocity control by Rosario Maggistro and Raffaele Pesenti -- Section II: Network and Organization theory -- 3. Organizational Routines and Networks by Lisa Balzarin -- 4. Entrepreneurship as networking? Theoretical insights in historical studies by Giovanni Favero -- 5. A network theory perspective to understanding art worlds, fields and markets by Massimiliano Nuccio -- Section III: The Network Organization -- 6. Networks and financial reporting by Chiara Saccon -- 7. Network boundaries for sustainability reporting: advances, challenges and future research by Marisa Agostini -- 8. Organizational misconduct and the network organization by Rachele Cavara and Francesco Zirpoli.
Keywords: Industrial organization; Social sciences -- Network analysis; Management; Organization; Network Research; Management